FULL DAY SCHOOL MANAGEMENT MODEL AT SMP ISLAM MANBAUL HIKMAH BREBES - Faid, Amrun; Slamet, Achmad; Prihatin, Titi (Educational Management, 2019)
This research was motivated by the problem of the lack of a community environment that requires parents to always be in charge of their children. The aim of the study was to Analyze how the Full Day School Program Planning and the Implementation of the Full Day School Program at SMP Islam Manbaul Hikmah Brebes. This research method used a qualitative descriptive approach. Also, the type of research the researchers used was a case study. This research was focused on Full Day School Program Plan and Implementation Work Plans at SMP Islam Manbaul Hikmah Brebes. Data was from the Fullday School Program and its data sources from the principal, teachers, students and students’ parents. The technique of collecting data was by observation, interview, and documentation. The validity technique was triangulation and it was analyzed with qualitative descriptive. The results showed that based on the results of observation, interview and documentation, it was said that, first, SMP Islam Manbaul Hikmah Brebes implemented the curriculum from the government and the school curriculum with additional subjects (Arabic, BTA, English comversation and computers). Second, Fullday school programs could develop and enhance intelligence of intelligence quotient (IQ), emotional quotient (EQ) and spiritual quotient (SQ) with various effective and actual educational innovations. It was suggested in this study that he implementation of Full Day School had to be evaluated in various perspectives, including psychological, sociological and economic aspects. Also, perspective related to curriculum adaptation could be evaluated.